PENGARUH PENGGUNAAN METODE DRILL BERBANTU MEDIA KARTU SOAL TERHADAP HASIL BELAJAR PESERTA DIDIK - Novianto Edwin Saputra; Ningrum Ningrum; Tiara Anggia Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Card-Based Media with Help of Drill Method is a good teaching tool for instiling certain habits. It is also the variety of methods for maintaining good habits. In addition, these methods can be obtained with a string, determination, opportunity, speed of skill. Card-Based Media with the Help of Drill Method can be used in general to obtain a set of materials or skill from those that have been studied and to obtain motoric skill. Based oh the survey result that the researcher did, the problem in this research was that there were still many students who had not yet completed the subjects of Accounting for class X Semester Odd SMK Negeri 1 Sekampung in the Academic Year of 2018/2019. The population was all students of class X of SMK Negeri 1 Sekampung which consists 164 students. In talking sampling uses a full sampling technique and the sample is the class X Accounting I as many as 27 Students as experiment class and X Accounting II as many as 29 Students as control class. The data of this research were collected by using data collection techniques, observation,interviews, documentation, and tests. Based on the results of these research, the hypothesis can be accepted because at a significant level of 5% (0,05) shows tcount > ttable, is 4,41>1,71. Thus it show that there is a positive influence on the use Card-Based Media with the Help of Drill Method on Learning Outcomes at X Grade Students in Accounting Subjects of SMK Negeri 1 Sekampung in the Academic Year of 2018/2019. Keywords: Card-Based Media with the Help of Drill Method, Learning Outcomes